Membangun Ekonomi Nasional yang Berkeadilan: Analisis Kritis atas Inovasi Kebijakan Kemenko Perekonomian dalam Bingkai Pancasila Menurut Ahmad Muhammad Mustain Nasoha: Building a Just National Economy: Critical Analysis of the Coordinating Ministry for Economic Policy Innovations within the Pancasila Frame According to Ahmad Muhammad Mustain Nasoha - Zulfa Amalia Firdausia; Hidayatun Musayanah; Ngaasya Masyrikul Jannah; Anisa ‘Ainnur Rohman (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Indonesia's economic development faces the challenge of maintaining a balance between growth, equity, and sustainability. In this context, the Coordinating Ministry for Economic Affairs (Kemenko Perekonomian) plays a strategic role in formulating and coordinating cross-sectoral policies oriented toward social justice, as mandated by Pancasila. This study aims to critically analyze the Coordinating Ministry's policy innovations in promoting inclusive and equitable national economic development. The research method used is qualitative, employing a literature review and policy analysis approach, including a review of official government documents, academic studies, and reports from international institutions related to Indonesian economic policy. The analysis shows that various policy innovations, such as strengthening the digital economy, reforming investment regulations, and post-pandemic economic recovery programs, have shown positive growth potential. However, implementation gaps remain, particularly in the areas of equitable distribution of development outcomes, protecting vulnerable groups, and environmental sustainability. In conclusion, although the Coordinating Ministry for Economic Affairs' policy innovations have contributed to the transformation of the national economy, the integration of Pancasila's social justice values still needs to be strengthened through oversight, public participation, and inter-institutional synergy to achieve inclusive, equitable, and sustainable economic development.